Beer, Brats, Cheese, and-- Baseball: The History and Impact of Baseball in Wisconsin - Sykora, Blake (My University, 2012)
From the 1800s baseball became a passion for the citizens of the United States. Wars, recessions and scandals could not bring down what is known as "America's Pastime." However baseball and other professional sports have been getting a bad name since historians and economist have started to look at the correlation between the team and the community. The notion of, "build us a new stadium at the cost of the tax payers or we are taking our team elsewhere" has been a common trend since 1950's. By looking at Appleton and Milwaukee this paper will look at the impacts baseball has on these communities both culturally and economically from 1966 to 2012.
Keywords: Baseball--Wisconsin--History; Baseball--Wisconsin--Economic aspects; Baseball--Wisconsin--Social aspects; Baseball--Wisconsin--Appleton; Baseball--Wisconsin--Milwaukee